ENGEMBANGAN DATABASE EVALUASI DIRI JURUSAN PENDIDIKAN TEKNIK BOGA DAN BUSANA FT UNY - Kapti Asiatun (Jurnal Pendidikan Teknologi dan Kejuruan, 2011)
ABSTRACTThis research aims at develping database of self evaluation among the students and lecturers of Food and Clothing Department with empirical testing. This database was implemented to five study programs, i.e. Food Engineering Education (S1), Clothing Engineering Education (S1), Food Engineering (DIII), Clothing Engineering (DIII) and Make Up Beauty (DIII). This research was using Reseach and Development Approach. The development of database was conducted through need analysis, planning, making program prototype, testing and evaluation. The software program to make database was using Microsoft Access 2007. The source of data was from the lecturers and the students. The data collection method was using need analysis data, documentation for planning, and datbase prototype creation, observation for program testing. Data analysis was conducted through qualitative descriptive analysis according to the research stages. The finding was in the form of database of self-evaluation consisted of students and lecturers data from Food and Clothing Department, which had been tested emphirically. The development stage had completed until the making of prototype of electronic database. The development procces had conducted throgh some stages, i.e. analysis, designing, implementation and evaluation.Keywords: database, Food and Clothing Department and self-eveluation